Highly Conductive Strong Healable Nanocomposites via Diels–Alder Reaction and Filler‐Polymer Covalent Bifunctionalization. Issue 3 (10th November 2021) - Faseela, K.P.; Benny, Aby Paul; Kim, Yongjun; Baik, Seunghyun
Abstract: Healable stretchable conductive nanocomposites have received considerable attention. However, there has been a trade‐off between the filler‐induced electrical conductivity (σ) and polymer‐driven mechanical strength. Here significant enhancements in both σ and mechanical strength by designing reversible covalent bonding of the polymer matrix and filler‐matrix covalent bifunctionalization are reported. A polystyrene‐block‐poly(ethylene‐ran‐butylene)‐block‐polystyrene grafted with maleic anhydride forms the strong reversible covalent bonding with furfuryl alcohol through the Diels–Alder reaction. Small (7.5 nm) and medium (117 nm) nanosatellite particles are generated by in situ etching of silver flakes, enabling electron tunneling‐assisted percolation. The filler‐polymer covalent bifunctionalization is achieved by 3‐mercaptopropanoic acid. Altogether, this results in high σ (108 300 S m −1 ) and tensile strength (16.4 MPa), breaking the trade‐off behavior. A nearly perfect (≈100%) healing efficiency is achieved in both σ and tensile strength. The conductive nanocomposite figure of merit (1.78 T Pa S m −1 ), defined by the product of σ and tensile strength, is orders of magnitude greater than the data in literature. The nanocomposite may find applications in healable strain sensors and electronic materials. Abstract : A highly conductive strong healable nanocomposite is realized by designing multiple covalent bonding between conductive filler and polymer matrix. This together with in situ formed Ag nanosatellite particles provide the nanocomposite with superior conductivity, high mechanical strength, and healability resulting in figure of merit of 1.78 T Pa S m −1, which is orders of magnitude higher than those reported in literature.